Economic Growth and Poverty: Does Formalisation of Informal Enterprises Matter? - Esther K. Ishengoma; Robert Kappel (German Institute of Global and Area Studies (GIGA), 2006)
The informal sector (IS) plays a significant role in developing countries viz. the provision of employment, income and supplying ignored markets. However, working and employment conditions within the sector are still poor. Its expansion and changing structures have thus drawn the attention of scholars and international policy makers to the factors hindering its formalisation. Among the factors addressed are the high costs of formalisation and the lack of incentives for operating in the formal sector. A variety of approaches have been adopted by different stakeholders to overcome these factors. This paper assesses these approaches along with the factors related to informality-formality trade-off and the issue of formalisation as a solution for firms' growth. By focussing on the problems faced by informal enterprises and the literature which addresses the options for accelerating the formalisation of informal enterprises, the paper will briefly summarise the weaknesses of these approaches. – – In Entwicklungsländern spielt der informelle Sektor (IS) eine bedeutende Rolle für Beschäftigung und Einkommen sowie in der Versorgung ansonsten missachteter Märkte. Gleichwohl sind Arbeits- und Beschäftigungsbedingungen in diesem Sektor in der Regel schlecht. Angesichts der Ausweitung und Veränderung der Strukturen des IS fragen daher Wissenschaftler wie politische Entscheidungsträger nach den Faktoren, die seine Formalisierung verhindern. Hierzu zählen unter anderem die hohen Kosten der Formalisierung sowie fehlende Anreize dafür, im formalen Sektor der Ökonomie zu operieren. Um diese Hindernisse zu überwinden, werden eine Reihe unterschiedlicher Ansätze angewandt. Dieser Beitrag analysiert diese Ansätze und fragt nach den Faktoren, die für die Entscheidung zwischen Formalisierung oder Verbleib im IS ausschlaggebend sind sowie nach der Bedeutung der Formalisierung für das Wachstum eines Unternehmens. Auf der Basis der Analyse der Probleme informeller Unternehmen sowie der Literatur über die Optionen zur Beschleunigung ihres Formalisierungsprozesses werden abschließend die Schwächen der verschiedenen Ansätze skizziert.
Keywords: L5; O17; O4; D2; E26; I3; 330; informal sector; small enterprises; formal and informal institution; cost of formalisation; informality; formality; poverty; economic growth; Wirtschaftswachstum; Armut; Armutspolitik; Informeller Sektor; Klein- und Mittelunternehmen; Schattenwirtschaft; Unternehmensentwicklung; Entwicklungsländer